Analisis Faktor Yang Mempengaruhi Kejadian Post Operatif Nausea and Vomiting (Ponv) Pada Pasien Sectio Caesarea Dengan Anestesi Spinal Di RSUD Tgk Chik Ditiro Sigli Kabupaten Pidie Provinsi Aceh - Eva Muntasir; Rahmaya Nova Handayani; Ema Wahyu Ningrum (Universitas Harapan Bangsa Purwokerto, 2023)
Postoperative nausea and vomiting (PONV) is a side effect that often occurs after anesthesia, with an incidence of approximately 1/3 of all patients undergoing surgery. This study aims to analyze the factors that influence the incidence of postoperative nausea and vomiting (PONV) in sectio caesarea patients under spinal anesthesia at Tgk Chik Ditiro Sigli Hospital, Pidie District, Aceh Province. This research method uses a type of cross-sectional analytic survey. The sampling technique in this study used the Accidental Sampling technique for 51 respondents from a total population of 103 patients. The instrument in this study was patient observation sheets obtained through observation through interviews and patient medical records. Data analysis was performed univariately and bivariately using the chi-square test. The results showed that there was an effect of age (p=0.001), parity (p=0.006) and anxiety (p=0.000) on the incidence of post operative nausea and vomiting (PONV) in sectio caesarea. This study concludes that there is an effect of age, parity and anxiety on the incidence of postoperative nausea and vomiting (PONV) at Tgk Chik Ditiro Sigli General Hospital, Pidie District, Aceh Province